Reimagining the World, Remaking the Region: Distinction and Difference in Early Modern and Modern Sindh - Rajani, Shayan. (2018)
Abstract: This dissertation is a longitudinal intellectual history of Sindh, a region on the western margins of South Asia, under Mughal, Kalhora, Talpur and British rule. The work revises academic and popular understanding of the region in South Asia as a static container for cultural particularity. Instead, the making and remaking of Sindh is examined as a series of intellectual projects that emerge from transregional engagement with universal ideas and values across shifting global dispensations. The articulation of theories of the region in Sindh are considered at three historic moments: the height of the Mughal Empire in the late sixteenth century, the era of decentralization in the eighteenth century, and the high noon of colonialism in the late nineteenth century. The work also attends to the social and intellectual milieus of Persian and Sindhi literary cultures that shaped these projects and to the operationalization of these ideas as markers of individual identity and as claims of political power.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of History.; Advisor: Ayesha Jalal.; Keywords: History, and South Asian studies.